Answer:
x=− 19/2 -9.500
Explanation:
- step one
- Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
3/4*x+5-(1/4+1/4*x)=0
3 1 1
((—•x)+5)-(—+(—•x)) = 0
4 4 4
- end of step one
- step 2 is to repeat the same thing as step one answer is also same as step one
- step 3
3.1 Adding fractions which have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
1 + x x + 1
————— = —————
4 4
3 (x + 1)
- ((— • x) + 5) - ——————— = 0
4 4
4
- 3 (x + 1)
- ((— • x) + 5) - ——————— = 0
- 4 4
- 5.1 Adding a whole to a fraction
- Rewrite the whole as a fraction using 4 as the denominator :
- 5 5 • 4
- 5 = — = —————
- 1 4
- Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
- Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
- 5.2 Adding up the two equivalent fractions
- Add the two equivalent fractions which now have a common denominator
- Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
- 3x + 5 • 4 3x + 20
- —————————— = ———————
- 4 4
- (3x + 20) (x + 1)
- ————————— - ——————— = 0
- 4 4
- 6.1 Adding fractions which have a common denominator
- Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
- (3x+20) - ((x+1)) 2x + 19
- ————————————————— = ———————
- 4 4
- 7.1 When a fraction equals zero ...
- Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.
- Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.
- Here's how:
- 2x+19
- ————— • 4 = 0 • 4
- 4
- Now, on the left hand side, the 4 cancels out the denominator, while, on the right hand side, zero times anything is still zero.
- The equation now takes the shape :
- 2x+19 = 0
- 7.2 Solve : 2x+19 = 0
- Subtract 19 from both sides of the equation :
- 2x = -19
- Divide both sides of the equation by 2:
- x = -19/2 = -9.500